Aktualisasi Pancasila Sila Pertama Ketuhanan Yang Maha Esa dan Sila Kedua Kemanusiaan yang Adil dan Beradab di Kelas Sekolah Dasar Negeri 169 Pelita Bandung - Amelia Nurul Hasanah; Karina Maharani, Ajeng Wulandari; Pandu Dharmawan, Husni Mubarok; Nur Isna Afni Fauziah, Vidia Zahra Nabila; Fajar Khairul Latif, Candra Nugraha; Diki Muhamad Ilham, Isnaini Hanifah; Dian Herdiana, Dewi Salamah (Yayasan Daarul Huda Kruengmane, 2025)
Pancasila, as the foundation and guiding philosophy of the Indonesian nation, must be realized in daily life so that its values are not merely normative but become grounded and serve as moral guidelines for society. The internalization of Pancasila values is crucial from the elementary school level, as children’s character at this stage is still highly malleable and can be effectively shaped. In this context, Group 3 of the Pancasila Education course at the State Islamic University of Sunan Gunung Djati Bandung conducted an activity aimed at actualizing Pancasila values, particularly the first principle, Belief in the One and Only God, and the second principle, Just and Civilized Humanity, for fifth-grade students of SDN 169 Pelita on November 4, 2025. The activities were carried out through the delivery of religious material, the habituation of polite behavior, and the cultivation of tolerance toward religious diversity. In addition, educational methods such as games, ice-breaking activities, prize-based quizzes, and hands-on practice of sharing food with the community were implemented as forms of internalizing humanitarian values. This activity aimed to enable students to understand Pancasila values in an engaging and enjoyable manner and to apply them in their daily lives.